Precarious work at a surgical center: implications for the organization and for the health of nursing workers - Elias Barbosa de Oliveira; Tatiane Xavier; Regina Celia Gollner Zeitoune; Joanir Pereira Passos; Bruno Rafael de Oliveira; Ana Rita Alves Ferreira (Revista Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to analyze the implications of precarious work for the organization of work and for the health of nursing professionals in a surgical center. Methods: qualitative, descriptive study in which the interview technique was applied on 30 nursing professionals from a surgical center in a university hospital located in the Southeast region of Brazil. The project was approved by the research ethics committee. Thematic content analysis was applied in the categorization of speeches. Results: precarious work in the surgical center negatively affects the organization of work due to staff turnover, loss of skilled talent, and the need for continuous training of temporary workers. It also affects the quality of care, leading to risks to patient safety and workers’ health.Final Considerations: it is important to make work conditions less precarious in order to minimize staff turnover and promote the quality of the service offered and the health of the worker.